The Practice of Mark Up Pricing in Determining the Selling Price of Gold Jewelry: The Perspective of Islamic Business Ethics - Eny Latifah; Moh. Efendy Baharuddin Yusuf (MultiTech Publisher, 2023)
The purpose of this research is to find out: (1) The practice of Mark Up Pricing in setting the selling price of gold jewelry at H. Abdul Mukhid's shop; (2) Islamic business ethics on the practice of Mark Up Pricing in setting the selling price of gold jewelry at H. Abdul Mukhid's shop. The research method used is qualitative with the type of study Case. The results of the study are (1) Pricing of H. Mukhid's gold jewelry shop using the Mark Up pricing method, with a profit of Rp20,000 for gold jewelry produced by himself, and a profit of Rp15,000-Rp20,000 for jewelry purchased (kulakan) at sales and loper; (2) Islamic business ethics in Mark Up Pricing for pricing by applying the principles of (a) Unity: working for worship and done in a halal way; (b) Balance: maintaining customer trust by providing pure gold products of the highest quality; (c) Free will: Free to determine the best staples and provide orders in a timely manner; (d)Responsibility, honesty: accepting resale on the condition that it does not come from stolen gold, (e)Truth, and honesty: honest in taking standard profits and not high either own production or from other parties, (f)Tolerance and friendliness: Buyers will be given recommendations if the store does not have the product they are looking for, and (g)Openness and freedom: Accepting criticism and suggestions from buyers in order to improve quality and service.